2013
DOI: 10.1016/s2095-3119(13)60371-8
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic Profiles and Antioxidant Activity of Buckwheat (Fagopyrum esculentum Möench and Fagopyrum tartaricum L. Gaerth) Hulls, Brans and Flours

Abstract: The extracts from hulls, brans and flours of Fagopyrum esculentum Möench (FEM, three varieties) and Fagopyrum tartaricum L. Gaerth (FTG, seven varieties) were screened for free and bound phenolic content or total phenolic content (TPC) , as well as 1, 1 diphenyl-2-picryl hydrazyl (DPPH) free radical scavenging activity and reducing power. Free phenolics were predominant in buckwheat hulls, brans and flours. FEM hulls extract exhibited the highest reducing power and DPPH free radical scavenging activity with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
34
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(46 citation statements)
references
References 24 publications
9
34
0
3
Order By: Relevance
“…Research evidence shows that according to total phenolic content and antioxidant activity in agricultural crops, buckwheat is of the most important plants. Li et al (2013) reported that extract of buckwheat husks has significantly more phenolic compounds than buckwheat grain with husks. Buckwheat husks exhibited the highest antioxidant activity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Research evidence shows that according to total phenolic content and antioxidant activity in agricultural crops, buckwheat is of the most important plants. Li et al (2013) reported that extract of buckwheat husks has significantly more phenolic compounds than buckwheat grain with husks. Buckwheat husks exhibited the highest antioxidant activity.…”
Section: Resultsmentioning
confidence: 99%
“…Buckwheat is an important dietary product, since it contains proteins with high biological value and balanced amino acid composition (Vojtíšková et al, 2012). It is also abundant in the bioactive compounds characterised by antioxidant properties (Li et al, 2013). Buckwheat husks constitute 17-20% of the total buckwheat production and is removed by impact milling.…”
Section: Introductionmentioning
confidence: 99%
“…Contrary to Velioglu and others () and Guo and others (), they did not find a correlation between the content of rutin and the antioxidative activity of buckwheat. In the studies of Li and others (), the correlation between the total content of phenolic compounds in hull and bran extracts and the antioxidative activity was not statistically significant; in the case of buckwheat flour a correlation was found between the content of polyphenols and free radicals scavenging DPPH ( r s = 0.79, P < 0.05).…”
Section: Resultsmentioning
confidence: 88%
“…A very weak correlation was seen between TPC and AA while a moderate negative correlation was observed between TPC and vitamin E content. It was reported that although many studies on different food samples show that AA is highly correlated with the components commonly associated with the antioxidant property of a food, it is not applicable for all due to the presence of other food components such as pigments, ascorbates, and others (Babbar, Oberoi, Uppal, & Patil, 2011;Li, Yuan, Yang, Tao, & Ming, 2013).…”
Section: Relationship Between Tpc Vitamin E Content and Aamentioning
confidence: 99%